'A Re-Specification of the Welfare State': Conceptual Issues in 'The Three Worlds of Welfare Capitalism'. Issue 2 (16th December 2014) - Powell, Martin
Abstract : In his path-breaking account of 'The Three Worlds of Welfare Capitalism', Gøsta Esping-Andersen (1990) aimed to provide a 're-specification of the welfare state'. This article examines the claim of Esping-Andersen that his account draws on the theoretical work of Polanyi, Marshall and Titmuss. It then explores the conceptual critique of Esping-Andersen which led to his 1999 revision, with its rather different theoretical underpinnings. It concludes that some of the theoretical underpinning of this work is unclear both in the work of Esping-Andersen and in subsequent accounts, resulting in a largely atheoretical debate. Concepts such as de-commodification do not appear to be clearly drawn from their stated 'parent' authors, and may not sum up the content or essence of welfare states. The 're-specification of the welfare state' must be a larger part of the strategy of the welfare modelling business in the future.